2019
DOI: 10.1088/1755-1315/403/1/012141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the efficiency of light traps of various design in corn agrocenosis

Abstract: The North Caucasus region in its natural and climatic conditions is a zone favorable for the cultivation of corn in Russia. Significant damage to corn plantings and crop quality is caused by a variety of pests. In connection with the annual crop losses caused by harmful insects, the development of methods for their monitoring and capture are relevant. The efficiency test of two designs of light traps based on super bright LEDs (conical and aspiration) was performed. As a result of the experiment, which lasted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Earlier researchers assert that conducting comparisons among different light traps offers a straightforward way to evaluate the influence of structural design on trapping efficiency [3]. Additionally, Pachkin et al [8] have observed that trap design significantly affects the efficiency of insect capture. Similarly, some other researcher viz.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier researchers assert that conducting comparisons among different light traps offers a straightforward way to evaluate the influence of structural design on trapping efficiency [3]. Additionally, Pachkin et al [8] have observed that trap design significantly affects the efficiency of insect capture. Similarly, some other researcher viz.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, nocturnal insects are collected exclusively through light trap. According toPachkin et al (2019) andMarchioro et al (2020), the light traps were more attractive for the representatives…”
mentioning
confidence: 99%